On the existence of an invariant manifold for weakly nonlinear matrix differential equations - Lipchan, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
For a system of nonlinear matrix differential equations with small parameter, we establish conditions of the existence of an invariant manifold in terms of the Green function.